Computational Methods and Experimental Measurements XIX 2019
DOI: 10.2495/cmem190011
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Small Fatigue Cracks in CU-5.5NI-1.28SI Alloy Round-Bar Specimens

Abstract: Cu-5.5Ni-1.28Si alloy processed by air-cooling after solution heat treatment was conducted to prevent the generation of discontinuous precipitates which bring a detrimental effect on mechanical properties, and stress-controlled fatigue tests were carried out at room temperature. The change in the surface damage during stressing was monitored by means of both direct observation and plastic replication technique, showing the crack initiation at grain boundaries, crystallographic slip planes and twin boundaries. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…where C 1 and n are material constants. The studies on small crack growth behaviour in various metals and alloys, such as carbon steels [21], low alloy steels [22], aluminium alloys [23], Ni-based superalloys [24], copper [25] and copper alloys [26], indicated that dl/dN of a small surface-crack in smooth specimens is determined by the term σ a n l. shows the growth data of a small surface-crack with the dl/dN vs. σ a n l correlation. The value of n in eqn (1) was 5.3 in all specimens.…”
Section: Tensile Properties Of Precipitate Strengthened Cu-6ni-15si Alloymentioning
confidence: 99%
“…where C 1 and n are material constants. The studies on small crack growth behaviour in various metals and alloys, such as carbon steels [21], low alloy steels [22], aluminium alloys [23], Ni-based superalloys [24], copper [25] and copper alloys [26], indicated that dl/dN of a small surface-crack in smooth specimens is determined by the term σ a n l. shows the growth data of a small surface-crack with the dl/dN vs. σ a n l correlation. The value of n in eqn (1) was 5.3 in all specimens.…”
Section: Tensile Properties Of Precipitate Strengthened Cu-6ni-15si Alloymentioning
confidence: 99%